The therapeutic potential of PX-478 in a murine model of pelvic organ prolapse - Wei-Min Fan; Yu-Qi Yang; Li-Wen Zhang; Xiao-Hui Mei; Ke Sun; Duan-Qing Wu; Ying Yang; Chun-Fang Duan; Jun Ye; Ru-Jun Chen (Journal of Obstetrics and Gynaecology)
Background Pelvic organ prolapse (POP), characterised by the downward displacement of pelvic organs, is a prevalent disorder that affects adult women. This study explored the therapeutic potential of PX-478, a selective hypoxia-inducible factor-1α (HIF-1α) inhibitor, in a murine POP model.Methods A murine POP model was established through ovariectomy, mimicking oestrogen deprivation. Fifteen C57BL/6J mice were randomly assigned to control, POP, and PX-478 groups. PX-478, targeting HIF-1α, was administered intravaginally. The analysis of fibroblasts, macrophage and inflammation was performed through Masson staining, immunofluorescence, and ELISA. Collagen distribution was assessed using Sirius Red staining. Expression levels of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMP-1) were determined through immunohistochemistry and western blot. Fibroblast proliferation and apoptosis were evaluated by CCK-8 assay and flow cytometry.Results PX-478 treatment significantly reduced vaginal length, indicating a therapeutic effect on POP severity. Masson staining revealed reduced fibrotic changes and collagen disruption in PX-478-treated mice. Immunofluorescence showed increased fibroblast markers (Vimentin, α-SMA) and collagen fibres by PX-478. Sirius Red staining indicated PX-478 mitigated damage to Type I and Type III collagen fibres. PX-478 significantly reduced MMP-2 and MMP-9 expression while increased TIMP-1. In macrophages, PX-478 decreased M1 and M2 markers (CD80, CD206) and IL-18 secretion. Fibroblasts exhibited increased proliferation, reduced apoptosis, and altered MMP/TIMP expression under PX-478 influence.Conclusion PX-478 demonstrates a therapeutic potential in the mice POP model. It reduces vaginal length, attenuates fibrosis, and modulates collagen synthesis. Its immunomodulation is evident through reduced M1 and M2 macrophages and suppressed IL-18 secretion.